What everyone needs to know about Islam - "Esposito, John L." (New York, 2011)
Since the terrorist attacks of September 11th, there has been an overwhelming demand for information about Islam, and recent events - the war in Iraq, terrorist attacks both failed and successful, debates throughout Europe over Islamic dress, and many others - have raised new questions in the minds of policymakers and the general public. This newly updated edition of What Everyone Needs to Know about Islam is the best single source for clearly presented, objective information about these new developments, and for answers to questions about the origin and traditions of Islam.
Keywords: Islam